Bio-inspired metallic cellular material with extraordinary energy dissipation capability - Feng, Jigang; Safaei, Babak; Qin, Zhaoye; Chu, Fulei; Scarpa, Fabrizio (Elsevier Science Sa, 2023)
Graphene coating on the skeleton of porous material opens the door to simply achieving high-performance composites. In this study, relying on the adhesive properties of polydopamine (PDA), PDA modified reduced graphene oxide (PDA-rGO) is adhered to the skeleton of nickel foam, of which the mechanical properties as well as the vibration damping and sound absorption performances are investigated. The mechanical test results reveal that the existence of coating leads to 240% and 59% increments of the compressive modulus and the yield strength, respectively. The enhancement of dynamic mechanical properties is also verified by dynamic me-chanical analysis (DMA). Moreover, in DMA tests, the loss factors of nickel foam coated with PDA-rGO are found to achieve up to 170% growth, and show excellent stability with increasing temperature, indicating the reliability of loss factor enhancement in harsh environment. The superior vibration damping performance of nickel foam coated with PDA-rGO is further confirmed by vibration tests. Furthermore, the coating is found to effectively boost the flow-resistance and improve the sound absorption capability of nickel foam in turn, this synergy results in a significant increase in the noise reduction coefficient for up to 73.3%. Hence, adhering PDA-rGO to nickel foam in the present study provides a promising strategy for the development of multi-functional and versatile metallic foam.
Keywords: Nickel foam; Mechanical properties; Vibration damping; Sound absorption; Polydopamine; Reduced graphene oxide